2010
DOI: 10.1260/1478-0771.8.2.135
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Documenting of Built Heritage: 3D Virtual Reconstruction of Architectural Details

Abstract: This paper examines 3D modelling of architectural elements with the help of parametric components. Such components may be useful within the framework of projects dealing with virtual 3D reconstruction of heritage monuments. Architectural components of the built heritage often have complex geometry. We studied the various geometrical shapes of a given architectural element, representative of a specific period and place. This study allowed us to identify the parameters and to implement parametric objects (in May… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 6 publications
0
37
0
2
Order By: Relevance
“…The parametric design of the building elements from the point cloud is a time-consuming and error-prone manual process, because there are currently no automation or software processes that can ensure a direct change from point cloud to full BIM models [80,81]. Therefore, once the 3D virtual models have been created, the libraries of the parametric elements should be generated under the concept of H-BIM.…”
Section: Bim To Heritage Buildingsmentioning
confidence: 99%
“…The parametric design of the building elements from the point cloud is a time-consuming and error-prone manual process, because there are currently no automation or software processes that can ensure a direct change from point cloud to full BIM models [80,81]. Therefore, once the 3D virtual models have been created, the libraries of the parametric elements should be generated under the concept of H-BIM.…”
Section: Bim To Heritage Buildingsmentioning
confidence: 99%
“…This limitation of BIM for existing buildings has motivated research in the development of new parametric libraries that would be suitable for existing and historic buildings. Various projects (Baik et al, 2014, Chevrier et al, 2010, Fai and Rafeiro, 2014, Murphy et al, 2013, De Luca, 2012 have shown that the development of new reusable parametric library objects supports high levels of detail (LoD) while decreasing the time of modelling. The parametric objects created by Fai & Rafeiro (2014) were created for the Autodesk Revit BIM software and contain very useful objects representing gothic style architectural windows.…”
Section: Parametric Librariesmentioning
confidence: 99%
“…The library created by Baik et al (2014), also for Autodesk Revit BIM software, contains parametric objects for heritage projects in the Al-Balad district of Jeddah City. An extensive library of parametric objects was created by Chevrier et al (2010). However, these objects are not suitable for BIM and were instead created with the MEL scripting language for Autodesk Maya software.…”
Section: Parametric Librariesmentioning
confidence: 99%
“…The method can be run also with other sources for 3D models such as photogrammetric surveys or existing CAD or procedural models [23]. The advantages of the methods with respect to the current state-of-the-art are twofold.…”
Section: A Procedures For Texturing 3d Models With Multispectral Imagesmentioning
confidence: 99%